PELAKSANAAN KEBIJAKAN PARIWISATA PEMERINTAH KOTA SABANG DALAM PERSPEKTIF SYARIAT ISLAM - Muhammad Irham (Sekolah Tinggi Ilmu Syariah Al-Hilal Sigli Aceh- Indonesia, 2015)
The other side implementation of Islamic law in Aceh is a strategic effortin formulating aspects of tourism as one of the mainstays in the developmentpolicy of the Islamic acehnese society today and in the future. Has not found aformula that is systematic, comprehensive, and practical implementation oftourism policies in general Aceh and Sabang in particular based on themethodological framework, the principles and values of authentic islamicteachings and integrative. In its manifestation, the implementation of tourismpolicies within the framework of Islamic law in Aceh has not arranged in aconcept that is complementary and integrated effectively and dynamically. Itrequired a breakthrough in realizing the concept of Islamic tourism policy